The knowledge social construction: An alternative in education - Mendoza García , Jorge (Consorcio de Universidades Mexicanas A.C., 2015)
In this written is argued many things about the knowledge of social construction: 1) the discussion about the mind from two different views: the individualist one and the psico-cultural one; 2) from psico-cultural stance is argued the importance and relevance of the signs ́andtools ́use in the mind configuration; 3) is discussed the language and dialogue pre-eminence in the ideas ́ interchange and the knowledge among people and its implication in the knowledge and social reality configuration; 4) it is characterized the use of an specific type of language, the words in a determined contexts and the use of another type of language which is the one of the concepts without context; 5) with these four late postulates is discussed the knowledge social construction purpose which is an alternative way. A critique tendency of tackling the learning in education nowadays. This perspective is characterized for putting the accent in language as a social practice. This also give an specific relevance to the discursive practices that are used in the classroom by teachers and pupils. At the end are outlined some job core ideas from this purpose.